The Role of Customer Interest in Mediating the Effect of the Implementation of Marketing Communication Strategies on Customer Decisions in Taking Retirement Loans at Semarang Steady Bank - Prasetya, Aldian Firdianto; Sadono, Teguh Priyo; Pramono , Bambang Sigit (Indonesian Journal Publisher, 2025)
This study aims to examine the role of customer interest in mediating the effect of integrated marketing communication (IMC) elements on customer decisions in taking retirement loans at Bank Mandiri Taspen, Semarang Branch. The IMC elements analyzed include advertising, promotion, direct marketing, word of mouth, and personal selling. Using a quantitative approach and Partial Least Squares (PLS) analysis with 145 purposively selected respondents, the study found that all IMC elements had a positive and significant effect on customer interest. However, none of the IMC elements directly influenced the decision to take credit. Customer interest plays a crucial mediating role, forming a full mediation pathway between most IMC elements and credit decisions, except for word of mouth, which exhibited partial mediation. These findings support the AIDA model and the hierarchy of effects theory, confirming that marketing communication impacts behavior through cognitive and emotional stages. The study provides theoretical reinforcement for IMC as a holistic strategy and offers practical insights for optimizing communication to influence customer behavior, particularly in the high-involvement financial service segment of retirees.